Factors Influencing Medication Adherence Among Children and Adolescents with Tuberculosis: Factors Affecting TB Medication Adherence in Youth - Rindani Claurita Toban; M. Alfian Rajab; Astri Yuliandini (CV. Paperhome Indonesia, 2026)
Background: Tuberculosis (TB) remains a major global health challenge, particularly in low-resource and geographically isolated areas such as Papua, Indonesia. Medication adherence among children and adolescents is crucial to achieving successful treatment outcomes and preventing drug resistance. However, adherence rates remain suboptimal due to various individual, familial, and healthcare-related factors. This study aimed to identify factors associated with medication adherence among children and adolescents with TB undergoing treatment at the Agats Public Health Center, Asmat Regency, South Papua.. Methods: A quantitative analytical observational study with a cross-sectional design was conducted from November to December 2024. The study included all 35 pediatric and adolescent TB patients registered at the health center, using a total sampling technique. Data were collected through validated questionnaires measuring knowledge, attitude, family support, the role of healthcare workers, and medication adherence using the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using univariate and bivariate analyses with the Chi-square test at a 95% confidence level (p ≤ 0.05). Results: Most respondents had low knowledge (77.1%), negative attitudes (85.7%), and poor family support (77.1%), while the majority perceived the role of healthcare workers as good (82.9%). Significant associations were found between knowledge (p = 0.033), attitude (p = 0.000), and the role of healthcare workers (p = 0.000) with medication adherence. Family support was not significantly associated with adherence (p = 0.068). Conclusion: Knowledge, attitude, and the role of healthcare workers significantly influence medication adherence among children and adolescents with TB. Although family support was not statistically significant, it remains an important contextual factor. Strengthening community-based health education, enhancing healthcare worker engagement, and empowering families are recommended to improve treatment adherence and outcomes, particularly in remote settings such as South Papua.